ANALYSIS OF STUDENT’S NEEDS IN WRITING AN ENGLISH DAILY ACTIVITY FOR THE FIRST YEAR STUDENTS OF SMP KARTIKA XX-2 MAKASSAR (Karya Ilmiah Mahasiswa (KIMA), 2024)
This research focuses on how far discovery learning method improves writing ability (daily activity) students of class VII SMP Kartika Wirabuana XX-2 Makassar. The objective of the research is to discover the effect of discovery learning method in improving writing ability (daily activity) students of class VII SMP Kartika Wirabuana XX-2 Makassar. This research is quantitative research. The population in this study was all students of class VII of Kartika Wirabuana XX-2 Makassar Junior High School which amounts to 68 people. The sample in this study was class VII A students of 12 people and class VII B amounting to 11 people. The instrument used in this study was a test. The purpose of this study is to find out how much influence the application of discovery learning methods to improve the writing skills of students of class VII junior high school Kartika Wirabuana XX-2 Makassar. The results of showed that the average score of students' writing ability with the application of the discovery learning smethod in the pre-test was 51.48 while in the post-test it was 78.70. After the application of the Discovery Learning Value method from Asymp. Sig. (2-tailed) of 0.025 < 0.05 then it can be said that the distribution research data is normal. From this study there is a significant difference in students between before and after the application of discovery learning methods.